The Implementation Of Target Recognation to Determine Enemy Coordinates Using Unmanned Aerial Vehicle (UAV) GALAK-24 Aircraft Cameras With Object Detection Method - Mahfudi, Isa; Arsyad, Mehmek Ali Akza; Purwanto, Bambang (Jurnal Telkommil, 2021)
Abstract – In this era of increasingly advance, camera technology to make it easier for the military to carry out attacks and defenses to destroy embattled opponents, for that is requires camera technology that can detect objects at once with the coordinates or position of the object cleary, so as to help troops to maximize attacks and maneuvers in war. This research is expected to develop GALAK-24 aitcraft equipped with enemy detection cameras and at the same time determine the position of enemy coorninates in real time in helping intelligence on the bettlefield, thus facilitating decision-making in warfare. The detection system uses object Detection methods to detect objects that are on the surface of the land crossed by the aircraft. The workings of this detection camera is to use the phython programming language thats is connected to the PC and connected also to the camera, when the aircraft makes a flight across enemy territory then the camera will capture the entire enemy territory so that there are vehicle object recorded as well, the target will be reported to calculate the enemy’s strength and enemy position. For security prosedures the aircraft will be flown at on altitude of 500 (m) to avoid enemy personnel fire and also reduce noise so as not to be heard by the enemy reporting the condition of enemy territory, enemy forces at the same time and sent to the operator.